The power of place in public leadership research and development. Issue 4 (31st October 2019) - Jackson, Brad
Abstract : Purpose: The purpose of this paper is to foreground place as a critical and central concern for public leadership research, development and practice. Design/methodology/approach: This invited essay draws on the author's own research and development work engaging in collaborative place-based interventions with academics, policy makers and practitioners. Findings: Place is one of six heuristic lenses in a Leadership Hexad that has been developed to interrogate and better understand leadership in a multi-dimensional manner. Place can provide an important theoretical and practical fulcrum for bridging both collaborative governance and collective leadership and public and political leadership as well as facilitating cross-sectoral leadership. Practical implications: This essay argues that more time and effort should be invested into researching and developing place leadership to complement the already extensive efforts to promote collaborative governance and place-based policy initiatives. Place leadership development should be genuinely cross-sectoral in its ambition and should focus on developing emerging and established leaders from the public, private, not-for-profit and indigenous sectors to tackle place-based problems and opportunities. Originality/value: This essay draws on experience undertaking academic research and conducting leadership development that draws from and feeds into policy and practice. It utilises research from geography, leadership studies, public management, public policy and political science to gain a more sophisticated understanding of the relationship between place and public leadership and how this can be harnessed to improve economic and social impact.